PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA UMKM RUFATA: Training in Preparing Simple Financial Reports for Rufata MSMES - Hartanti, Rina; Sipayung, Emma Saur Nauli; Tajib, Erny (PUAN INDONESIA, 2024)
The important role of MSMEs in the history of reducing unemployment rates during the economic crisis in Indonesia and as a booster for economic recovery after the Covid-19 pandemic cannot be separated from the creativity and hard work of MSME entrepreneurs in maintaining the sustainability of their businesses. The sustainability of MSME businesses will be maintained if MSME entrepreneurs not only carry out various innovative efforts to sell their business products or services but must also be able to manage the financial results of their business by increasing their knowledge and skills in preparing financial reports for all economic transactions of their business. Likewise, Rufata MSME entrepreneurs really need training from teachers or lecturers. The Bachelor of Accounting Study Program, Faculty of Economics and Business, Trisakti University collaborates with the Rufata MSME Coordinator, Cikokol Village, Pancoran District, South Jakarta, held a Community Service (PKM) program with the title: "Training on Preparing Simple Financial Reports for Rufata MSMEs", so that MSME entrepreneurs are not only able to make simple financial reports from economic transactions of their business businesses correctly in accordance with SAK EMKM, but also can analyze and evaluate the sustainability of their business and can make appropriate decisions for business development. The results after the implementation of the PKM were in line with expectations, where participants were very enthusiastic about asking questions about the accounting process, the concept of business entities and answering the given accounting exercise questions, where the results of the assessment obtained an average score of 58 to 73